TRANSFORMATION AND REVITALIZATION OF SERVICE QUALITY IN THE DIGITAL ERA OF REVOLUTIONARY DISRUPTION 4.0 - Sila, I Kadek; Martini, Ida A.O. (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2020)
Banking services are currently experiencing changes in the midst of technological advancements that have changed people's behavior to use digital technology in everyday life and have even become a lifestyle, especially for the millennial. This change requires the BPR to carry out a transformation and revitalization of service quality in the era of digital disruption revolution 4.0. The aim of this study was to describe the readiness, strategies, and inhibiting factors faced by Banks in conducting the Transformation and Revitalization of Service Quality in the Digital Era Revolution 4.0. The results of this study from interview, observation, documentation are the preparation in conducting Transformation and Revitalization of Service Quality in the Era of Digital Disruption Revolution 4.0 are done step by step, by implementing partnership and collaboration strategy, internal reinforcement, digital innovation and improving the quality of people, product, and process so banks have the competitiveness and competitive products in the era of digital revolution. Capital and human resources are factors in the development of digital-based product and service innovations that were demanded in the Revolution 4.0 era.Â Keywords: Transformation, Revitalization, Service Quality, Digital Era, Revolution 4.0, Banks